Writing Daily Status On Social Media: Code-Mixing Phenomena At Sekolah Advent Makassar - Carolina Mewengkang; Sukardi Weda; Sudriman Maca (Jounal of Primary Education, 2023)
The purpose of this study was to analyze the using of code mixing on social media at the Elevent Grade of Sekolah Advent Makassar. This research applied descriptive qualitative research. Data collection technique by using an observation and interview. Purposive sampling is the technique to chose the subject. There were 5 Students as subject from 26 students.  The data  was taken by the screeshot observation to know their type of code mixing on Instagram. The researchers interviewed for the 5 students to know about the students’ reasons using code mixing in writing status. Based on the results of the observation, interviews and recording that have been conducted, students used type of code mixing dominant is insertion in writing daily satus and ther reasons students’ used code mixing in writing daily status are less of English vocabulary and social community. The researcher found that the highest reason of using code mxing by the students is that they have less English vocabulary. This proves that the role of social media and community is very important at this ages and Students’ involvement in every situation to express their languages